A Comprehensive Investigation on Image Caption Generation using Deep Neural Networks - Batista, Andreza; Costa, Lucas Hilario da; Rodríguez, Demóstenes (INFOCOMP Journal of Computer Science, 2022)
Currently, Voice over IP (VoIP) is one of the most used communication services, however, its quality is related to several external factors that cause various types of degradation of the voice signal, directly affecting the quality of experience (QoE) of users. In order to classify the quality of the voice signal transmitted in a VoIP communication affected by packet loss, two deep learning network models (DL - Deep Learning) were implemented. The models were developed using a deep neural network model (DNN), through which the analysis of the voice signal affected by the packet loss rate (PLR) of the degraded signals, so it was possible to classify them into four different classs according to the user’s experience. Thus, two databases were prepared, each containing four distinct classs. One of these was prepared with the ITU-T P.862 recommendation database files with different packet loss rates, and the other database was prepared with the ITU-T P.501 recommendation files according to the index MOS of Mean Opinion Score (MOS) of each degraded file. The results obtained from the model for the database prepared by the packet loss rate was 94% accuracy in model validation, while the model results for the database prepared by MOS the result obtained was 91% of accuracy. In a comparison with the results obtained by the P.563 algorithm and the results obtained by the P.862 algorithm, it was possible to obtain an average of 53.21% accuracy for the P.563 algorithm in comparison with the classification results of the algorithm P.862. Through the results obtained, it can be concluded that the generated models were able to classify the packet loss rate and the MOS index in a non-intrusive way and with a great accuracy rate. Concluding that the generated models are able to determine the MOS of the degraded voice files more efficiently than the P.563 algorithm. Keywords: VoIP, Voice Quality, ITU-T P.862, ITU-T P.563, ITU-T P.501, Deep Learning, Machine Learning